PENGGUNAAN KONJUNGSI KOORDINATIF DALAM PENYUSUSNAN TEKS ANEKDOT SISWA KELAS X DI KOTA MATARAM - Adha, Isna; Mahsun, Mahsun; Mahyudi, Johan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to measure students' ability to produce text in Indonesian language learning. The focus of this research is to describe students' ability to write anecdotal texts by utilizing coordinate/equivalent conjunctions. Text-based learning has been implemented for a long time in Indonesia and this research was conducted to see if students' ability to produce text has increased. The population of this research is secondary education students in Mataram City and to facilitate the course of research selected 40 students as a sample provided that all students have received the same learning. This research is included in qualitative research. The results of this study showed that students' ability to produce anecdotal texts in the category was lacking. It is hoped that this research has success in helping to improve students' writing ability in producing a text.